Emergent Management of Intracardiac Thrombosis during Liver Transplantation. (14th December 2016) - Protin, Caroline; Bezinover, Dmitri; Kadry, Zakiyah; Verbeek, Thomas
Abstract : Intraoperative thromboembolism is a well-documented complication associated with orthotopic liver transplantation (OLT) but its identification and intraoperative treatment are still an emerging topic in anesthesia. Intracardiac thrombus during OLT is associated with a high mortality rate. There are only a few reports describing the successful management of thromboembolism during OLT. We describe a case where routine intraoperative transesophageal echocardiography during a live donor liver transplantation enabled early detection of an intracardiac thrombus with subsequent successful heparin treatment. Our case suggests that if an intracardiac thrombus is identified early (before hemodynamic instability occurs), the use of IV heparin may be a safe therapeutic option.